Proteostasis During Cerebral Ischemia - Thiebaut, Audrey M.; Hedou, Elodie; Marciniak, Stefan J.; Vivien, Denis; Roussel, Benoit D. (Frontiers in Neuroscience, 2019)
Cerebral ischemia is a complex pathology involving a cascade of cellular mechanisms, which deregulate proteostasis and lead to neuronal death. Proteostasis refers to the equilibrium between protein synthesis, folding and transport; and protein degradation. Within the brain proteostasis plays key roles in learning and memory by controlling protein synthesis and degradation. Two important pathways are implicated in proteostasis’ regulation: the unfolded protein response (UPR) and macroautophagy (called hereafter autophagy). Both are necessary for cell survival, however their overactivation in time or intensity often leads to cell death. Moreover, UPR and autophagy can activate and potentiate each other to worsen the issue of cerebral ischemia. Better comprehension of autophagy and ER stress will allow therapeutic strategies for stroke both at the acute phase and during recovery. The interest of this review is to summarize the latest therapeutic advances implicating ER stress or autophagy in cerebral ischemia. In addition, we discuss the interest to study proteostasis as a single pathway rather than studying either ER stress or autophagy in stroke.